Reviews. Issue 2 (1st September 2014) - Norman, Kelsey P.; Marino, Sara
Co-Ethnic Strangers: Immigrant Exclusion and Insecurity in Africa, Claire L. Adida (2014) Cambridge: Cambridge University Press, 188 pp. ISBN: 9781107047723, h/bk, £55.00Migrant Memories. Cultural History, Cinema and the Italian Post-War Diaspora in Britain, Margherita Sprio (2013) New York and Oxford: Peter Lang, 290 pp. ISBN: 9783034309479, p/bk, £45.00